The Emerging Use of ASC/Scaffold Composites for the Regeneration of Osteochondral Defects - Rahman, Gohar; Frazier, Trivia P.; Gimble, Jeffrey M.; Mohiuddin, Omair A. (Frontiers in Bioengineering and Biotechnology, 2022)
Articular cartilage is composed of chondrocytes surrounded by a porous permeable extracellular matrix. It has a limited spontaneous healing capability post-injury which, if left untreated, can result in severe osteochondral disease. Currently, osteochondral (OC) defects are treated by bone marrow stimulation, artificial joint replacement, or transplantation of bone, cartilage, and periosteum. While autologous osteochondral transplantation is also an option, it carries the risk of donor site damage and is limited only to the treatment of small defects. Allografts may be used for larger defects; however, they have the potential to elicit an immune response. A possible alternative solution to treat osteochondral diseases involves the use of stromal/stem cells. Human adipose-derived stromal/stem cells (ASCs) can differentiate into cartilage and bone cells. The ASC can be combined with both natural and synthetic scaffolds to support cell delivery, growth, proliferation, migration, and differentiation. Combinations of both types of scaffolds along with ASCs and/or growth factors have shown promising results for the treatment of OC defects based on in vitro and in vivo experiments. Indeed, these findings have translated to several active clinical trials testing the use ASC-scaffold composites in human subjects. The current review critically examines the literature describing ASC-scaffold composites as a potential alternative to conventional therapies for OC tissue regeneration.